2003
DOI: 10.1001/archinte.163.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction in Human Immunodeficiency Virus–Infected Patients

Abstract: Patients infected with HIV sustain AMI at a young age and have a benign in-hospital course. Although HIV-infected patients have a higher incidence of postdischarge ischemic events, restenosis, and stent thrombosis, the intermediate-term mortality is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 22 publications
1
61
1
5
Order By: Relevance
“…[11][12][13][14][15] These studies demonstrated that HIVinfected patients had the same treatment at the acute phase, but that the rates of recurrent AMI and urgent percutaneous coronary intervention (PCI) during follow-up were higher than in HIV-uninfected patients. Unfortunately, in-hospital mortality could not be studied because there were too few patients (between 20 and 103).…”
Section: Clinical Perspective On P 1774mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] These studies demonstrated that HIVinfected patients had the same treatment at the acute phase, but that the rates of recurrent AMI and urgent percutaneous coronary intervention (PCI) during follow-up were higher than in HIV-uninfected patients. Unfortunately, in-hospital mortality could not be studied because there were too few patients (between 20 and 103).…”
Section: Clinical Perspective On P 1774mentioning
confidence: 99%
“…Unfortunately, in-hospital mortality could not be studied because there were too few patients (between 20 and 103). [11][12][13][14][15][16][17] The main objective of the present study was to determine the influence of HIV infection on in-hospital mortality within a large national cohort of patients with AMI. The second objective was to compare the 1-year prognosis in HIV-infected patients with that in HIVuninfected patients.…”
Section: Clinical Perspective On P 1774mentioning
confidence: 99%
“…It is usually more difuse and is associated with circumferential-intimal thickening, atherosclerotic plaques and abnormal proliferation of the smooth muscle. The muscles with luminal protrusions share several similarities with cardiac transplant vasculopathy [34][35][36][37][38]. Reports have suggested that the most common initial presentation of the HIV patient with CAD is acute myocardial infarction and its mortality can go as high as 24%.…”
Section: Hiv and Atherosclerotic Coronary Artery Diseasementioning
confidence: 99%
“…Los pacientes con factores de riesgo adicionales -como hipertensión, diabetes, tabaquismo e hiperhomocisteinemia-pueden tener un riesgo mayor para desarrollar síndromes coronarios agudos o infartos cerebrales, por la acelerada aterosclerosis que en ellos se produce (2,14,(17)(18)(19)(20)(21)(22) .…”
Section: Infarto Agudo De Miocardiounclassified